Cognitive responses to hypobaric hypoxia: implications for aviation training - Neuhaus, Christopher; Hinkelbein, Jochen (Psychology research and behavior management, 2014)
The aim of this narrative review is to provide an overview on cognitive responses to hypobaric hypoxia and to show relevant implications for aviation training.
Gesehen am 09.10.2020